Sila socialnosti v luči sociolingvistike in sociologije jezika - Tomc, Gregor (Teorija in praksa, 2018)
The author presents the role language information processing plays in the emergence of consciousness that distinguishes us from other developed animals. He explains how consciousness functions (how speech shapes our awareness of awareness), then presents two basic approaches to research (sociolinguistics and sociology of language), conscious cognition (thinking and sensation/emotion) and the evolutionary function of language (which is limited to the domains of production and reproduction). In the concluding remarks, the author states that social science of the future will be based on sociogenomics, social neuroscience and social lingustics.
Keywords: Genomics; Genomika; Neurosciences; Nevroznanosti; Sociolinguistics; Sociolingvistika; Sociologija jezika; Sociology of language